Indonesian EFL’s Learning Strategies and Personality Types in Achieving TOEFL Score Above 500 - Parmadi, Alifia Rimas; Kepirianto, Catur (Universitas Pendidikan Ganesha, 2023)
There are many English proficiency exams available, including the TOEIC, TOEFL, and IELTS. TOEFL is one of the most well-known English proficiency tests in Indonesia, which is taken for both academic and professional requirements. The average TOEFL score for Indonesian students is still below the global norm of 500. Based on the problems and the difficulties faces by most of Indonesia learners, this study tries to analyze the learning strategies used by learners who successfully achieve TOEFL scores above 500. This study also delves into the learner's personality types in order to understand the characteristics of each type that affected their learning strategy. The 15 participants are randomly selected from Indonesian EFL students between the ages of 20 to 25. The participants must have taken the TOEFL test and received the score above 500. Both quantitative and qualitative writing are used in this study. The quantitative method used in analysing the data collection, the researchers employed descriptive statistic data analysis in Excel to find out the mean. Two different types of instruments were used to collect the data: Oxford's Strategy Inventory for Language Learning and the Myers-Briggs Type Indicator. The result of this study shows; metacognitive strategy as the dominant strategy utilised by the majority of learners and there are 8 personality types such as; ISTJ, INFJ, ISFP, INFP, ENFP, ESTJ, ESFJ, and ENFJ.